Cancer-Specific Concerns and Physical Activity Among Recently Diagnosed Breast and Prostate Cancer Survivors - Ottenbacher, Allison (2012)
BACKGROUND: Cancer treatment-related side effects may have a negative impact on quality of life among cancer survivors, and may limit participation in physical activity. HYPOTHESIS: Cancer-specific concerns will be reduced throughout a 10-month diet and exercise intervention among recently-diagnosed cancer survivors. Additionally, participants reporting greater levels of physical activity will also report fewer cancer-specific concerns. STUDY DESIGN: This study is an exploratory analysis of 452 recently diagnosed, early stage breast and prostate cancer survivors who participated in the FRESH START diet and exercise trial. Data were collected at baseline and 1-year follow-up via telephone administration of the Functional Assessment of Cancer Therapy (FACT) instrument and the 7-Day Physical Activity Recall. RESULTS: At baseline, chief concerns among prostate cancer survivors included ability to have an erection (mean score [SD]: 1.0 [1.3]) and urinary frequency (2.5 [1.4]), whereas among breast cancer survivors eminent concerns were not feeling sexually attractive (2.0 [1.3]) and worry about cancer in other members of their family (2.1 [1.3]). At 1 year, there was a significant improvement in cancer-specific concerns on breast cancer specific-concerns (p<0.01), but not on prostate cancer-specific concerns. Physical activity (PA) was generally not related to cancer-specific concerns, though at baseline women who were self-conscious about their dress had higher levels of PA, whereas men reporting issues with incontinence reported lesser increases in PA in response to the intervention. CONCLUSION: While cancer survivors have several cancer-specific concerns, these concerns diminish over time, especially among breast cancer survivors. Furthermore, this reduction appears independent of changes in physical activity. Among prostate cancer survivors, incontinence is a significant barrier that hinders benefit from PA interventions. Thus, there is a need either for medical interventions to ameliorate incontinence or for behavioral interventions to address this issue among survivors, especially given the importance of PA for overall health.